LAYOUT SECTION COMPOSITE BEAMS WITH A VIEW TO OPTIMIZING THE STEEL - Alla Ilinichna Gavrilova; Svetlana Vyacheslavovna Guteneva (Вестник Северо-Кавказского федерального университета, 2022)
In the article for the composite steel beams is given the formula, which makes it possible one time to determine a maximally possible effective value of the calculated strength of materials of beams to bending Ry and to obtain optimal solution.